Visualization of Guimaras State University Community Extension Services: Basis for Expansion - J. Forca, Adrian; Karlitasari, Lita; Putra, Gustian Rama (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2024)
The Study Visualization of Guimaras State University Community Extension Services: Basis for Expansion was conducted to visualize the dataset of the GSU Extension Services office to serve as basis for the unit to expand its scope towards the number of communities to be adapted, number of training to be conducted, number of communities adapted vs number of communities that are not adapted and the number of programs implemented in every community cluster. To visualize such, the researcher made use of Tableau Public in which, a descriptive component was used in the study to determine the effectiveness of the visualized information. Visualization was conducted and respondents of the study agreed that the visualized information is effective that can serve as the basis for the GSU Extension Services to expand its present services so that more communities to be adapted and uplift their quality of life.